2021
DOI: 10.3390/ijerph18179098
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Colorectal Cancer Diagnosis during the COVID-19 Pandemic in Alberta: A Framework for Analyzing Barriers to Diagnosis and Generating Evidence to Support Health System Changes Aimed at Reducing Time to Diagnosis

Abstract: The frequency of colorectal cancer (CRC) diagnosis has decreased due to the COVID-19 pandemic. Health system planning is needed to address the backlog of undiagnosed patients. We developed a framework for analyzing barriers to diagnosis and estimating patient volumes under different system relaunch scenarios. This retrospective study included CRC cases from the Alberta Cancer Registry for the pre-pandemic (1 January 2016–4 March 2020) and intra-pandemic (5 March 2020–1 July 2020) periods. The data on all the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Subsequent studies have confirmed the predicted diagnostic delay [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In a study conducted in Taiwan, Tsai et al [ 9 ] reported that admissions to breast outpatient clinics in hospitals decreased by 37% during the lockdown period, and breast cancer screening decreased by 22%.…”
Section: Discussionmentioning
confidence: 86%
“…Subsequent studies have confirmed the predicted diagnostic delay [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In a study conducted in Taiwan, Tsai et al [ 9 ] reported that admissions to breast outpatient clinics in hospitals decreased by 37% during the lockdown period, and breast cancer screening decreased by 22%.…”
Section: Discussionmentioning
confidence: 86%
“…To improve the diagnostic capacity of colonoscopy across the health system, a 140% increase in monthly colonoscopy volumes is needed for a period of 3 months. 19 This requires substantial and unlikely health system changes. For instance, there is an option for screening programs to extend the invitation interval, which has demonstrated no association with an increase in the interval CRC rate.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable proportion of the oncological patients had a diminished medical attention throughout the ongoing SARS-CoV-2 pandemic, consistent with the estimations and forecasts. In addition, a significant number of patients who were initially diagnosed with colorectal cancer that was curable in its early stages may have become incurable in its later stages due to missed appointments for colorectal cancer screening and elective surgery, deliberate refusal of treatment, or deliberate delay of treatment out of fear of COVID-19 [ 25 ]. Although we observed a significantly higher proportion of stage IIa cancers in 2020, compared to the previous year and 2021, the difference is likely to happen just due to chance alone, since the overall comparison of colorectal cancer staging during the three-year study period was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%